Brand Equity Research Using Online Customer Ratings of Spanish Hotels - Soler-García, Ismael Pablo; Gemar-Castillo, Germán (Wiley, 2017)
This study sought to create and test a customer-based brand equity model for Spanish hotels with TripAdvisor data. Using a sample of 1514 hotels and structural equation modelling with an asymptotically distribution-free method, a valid basic, unified model was developed. The results confirm the viability of online data for brand equity research. These data reduce the cost of data capture, allowing the collection of a large amount of data and the creation of more dynamic models. The results also show that aspects of brand equity are now under the control of users, a finding that requires further research.
https://openpolicyfinder.jisc.ac.uk/id/publication/7482
Keywords: Marcas (Marketing); Hoteles - Marketing; Reputación digital; TripAdvisor; Spain; Customer-based brand equity; Strucutral equation modelling; Customer review; Online